Clinico-Biochemical Study of Iodine Nutritional Status of Tribal Communities of Santhal Pargana Region of Jharkhand, India - Rao, T.V.R.K.; Goswami, Jayashree (Asian Journal of Chemistry, 2011)
Iodine nutritional status of the tribal communities under different age-group viz., 6-12, 13-18, 9- 39 and 40 yr and above of Dumka district of Santhal Pargana Division of Jharkhand, India, has been studied. Urinary iodine excretion levels and serum protein-bound iodine levels were estimated. Iodine content of the common salt samples consumed by the tribals was determined. Goiter prevalence among the target population was also assessed. Over all median urinary iodine excretion level was found to be at 13.49 μg/dL and median serum protein-bound iodine level was at 5.1 μg/dL. 76 % of the common salt samples contained iodine at 15 ppm and above. Total goiter prevalence was found to be at 3.25 %. The results suggest that there is no biochemical iodine deficiency and the goiter prevalence is at very mild level in the target population. The tribals, however, should be further encouraged to consume iodized salt.